A comparative study of tungsten carbide and carbon nanotubes reinforced Inconel 625 composite coatings fabricated by laser cladding. (August 2021) - Zhou, Shaowei; Xu, Tianyu; Hu, Chang; Wu, Han; Liu, Huailiang; Ma, Xiuquan
Highlights: The differences of wettability among the three samples were presented. The strengthening mechanisms of these two particles were investigated. The main secondary compounds of reinforcement particles were discussed. The effect of grain refinement on mechanical properties was concluded. Abstract: Laser cladding with wire presents clear advantages in economic efficiency and cleanliness over the powder-based system. To find the best coating performance, the Inconel 625 composite coating, and two typical metal matrix composite (MMC) coatings reinforced respectively by tungsten carbide (WC) and carbon nanotubes (CNTs) were fabricated by an off-axis wire cladding system. The differences of morphology, microstructure and mechanical properties among the three samples were investigated. The results showed that the morphology of clad coatings with reinforcement powder generally presented desirable geometric characteristics. The clad coating with WC powder, in particular, presented better wettability compared with the other samples. The main secondary compound of WC dissolution was W2 C, which was mainly distributed at grain boundaries. The mechanical properties of powder reinforced MMC coatings were significantly improved. Compared with the Inconel 625 specimen in coating area, the yield strength of the two MMC coatings was improved by 36.3% and 23.4% respectively. In addition, the average microhardness of WC/Inconel 625 coating showed an obvious increase to 589 HV.